Analisis Kesalahan Berbahasa Jawa Ranah Fonologis dalam Lingkungan Masyarakat Ponorogo - Wanti, Luki Irma; Setyanto, Suroto Rosyd; Mahanani, Endah Normawati (STKIP PGRI Ponorogo Press, 2024)
This research is a case study research with a descriptive qualitative research method that focuses on phonological studies. This research aims to describe the forms of phoneme pronunciation errors in Javanese society, the factors that cause them and how to overcome these phoneme errors. This research shows that 25% of pronunciation errors occur in vowel phonemes and 75% occur in consonant phonemes. Factors that cause phoneme pronunciation errors in Javanese society include environmental factors, namely family, economic factors and also the person's own lack of ability to learn Javanese.